Incidence and risk factors of gestational diabetes in Karnataka Institute of Medical Sciences, Hubli - G, Vinaya; M., Surekha S.; Chiniwal, Shivaganga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Gestational diabetes is essentially the development of diabetes in pregnancy with a return to normal glucose tolerance after delivery. Objective of the study was to know incidence and risk factors of gestational diabetes in Karnataka Institute of Medical Sciences, Hubli. Methods: This prospective study conducted in KIMS Hubli, for a period of one year from October 2009 to November 2010, in all pregnant women attending OPD of OBG Department. The number of cases included in the study was 200. Results: Incidence of GDM was found to be 3.5% in the 200 patients studied. Patients were in the age group 18-36 yrs. There was increasing in the incidence after 25 yrs. There is gradual increase in prevalence of GCT positive case with increasing age. 60% of the patients had risk factors. Risk factors of importance were positive family history 40%, BMI>27 was 37.5%. Conclusions: Gestational diabetes mellitus can be present in patients without risk factors. Hence the need for universal screening. Glucose challenge test with 75g glucose at 2 hours is highly sensitive in detecting GDM.